Developments of terahertz metasurface biosensors: A literature review - Zhang Zhongquan; Zhao Rui; Cong Mengyang; Qiu Jianfeng (Nanotechnology Reviews, 2024)
Terahertz metasurface (THz-MS) biosensor is a hybrid technology that combines terahertz time-domain spectroscopy and metasurface for the detection of biomolecules and cells. Compared with traditional strategies, it is label-free, non-invasive, time-saving, and easy to operate. However, three fundamental issues, namely, low sensitivity, low specificity, and drastic water absorption, hinder the development of THz-MS biosensors for clinical application. Recently, numerous studies of THz-MS biosensors have been performed to solve these problems, and the results show great potential for the sensitive detection of nucleotides, proteins, and cells. Therefore, it is important to summarize the development of THz-MS biosensors in biomedical detection. In this review, we summarized the mechanism, manufacturing, and implementation of THz-MS biosensors. Then, strategies to improve the sensitivity, selectivity, and means to reduce water absorption are presented. Sensitivity can be improved by suppressing electromagnetic radiation and strengthening the interaction between target molecules and meta-atoms. Antibodies and aptamers are the most effective strategies for improving specificity. Microfluidics and hydrogels are two potential ways to reduce the water absorption. Subsequently, the applications of the THz-MS biosensors for the detection of nucleotide, proteins, and cells are summarized. Finally, the prospects for the future development of THz-MS biosensors are outlined.